A MoNbZr / Zr nano-layered material and preparation method thereof

MoNbZr and Zr layers are alternately deposited through magnetron sputtering technology to form MoNbZr/Zr nanolayered materials, solving the problems of limitations in the existing technology of interface structure and poor comprehensive performance of materials, and achieving high purity, uniform density and excellent integration Properties of nanolayered materials.

CN116145076BActive Publication Date: 2025-02-14XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310179780.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-02-14
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The method of preparing nanolayered materials with various interface structures in the prior art is very limited, and the comprehensive performance of the prepared materials is poor, making it difficult to meet the requirements of high strength, high plasticity and high thermal stability.

Method used

MoNbZr and Zr layers are alternately deposited in a high vacuum environment through magnetron sputtering technology to form alternately stacked nanolayered materials, controlling the layer thickness and interface structure to improve the overall performance of the material.

Benefits of technology

The prepared MoNbZr/Zr nanolayered material has high purity, uniformity and density, strong interface bonding, excellent comprehensive performance, including improved radiation resistance and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116145076B_ABST
    Figure CN116145076B_ABST
Patent Text Reader

Abstract

The invention discloses a MoNbZr / Zr nano-layered material and a preparation method thereof. The MoNbZr / Zr nano-layered material is prepared by depositing on a clean silicon substrate by a magnetron sputtering deposition method. Ar+ ions bombard a target material to cause elastic collisions with MoNbZr / Zr atoms, further generating a collision cascade, whereby the sample atoms are excited and reversely deposited onto the substrate. MoNbZr atoms and Zr atoms are deposited in sequence to alternately form multilayer nano-layered materials with different modulation periods, different interface structures, and different phase compositions. High-density plasmas such as secondary electrons generated by sputtering circulate in the form of cycloids under the combined action of mutually perpendicular electromagnetic fields, and do not contact the substrate. Therefore, the ionization efficiency is high and the deposition rate is fast. The invention not only successfully prepares nano-layered materials with different phase compositions, but also the obtained nano-layered materials are uniform and dense, with clear interface structures and excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface modification, and in particular relates to a MoNbZr / Zr nano-layered material and a preparation method thereof. Background Art

[0002] The rapid development of society has put forward more stringent requirements on the comprehensive performance of metal structural materials, such as high plasticity, high thermal stability and high strength. In order to improve the mechanical strength of metal materials, grain refinement and amorphization are usually used, but at the same time, plasticity is sacrificed. Strength and plasticity depend largely on the dislocation-defect interaction in crystalline materials and shear band deformation in metallic glasses. In order to meet these challenges, nanostructured materials have become important candidate materials.

[0003] Nanostructured materials are hailed as the new materials of the 21st century. As the characteristic size of the microstructure is reduced to the nanoscale, the interface will become the main structural unit of nanostructured materials. In recent years, interface engineering, which regulates performance by designing interface structures, has gradually become an important way to improve the performance of nanostructured materials. Among them, nano-layered materials themselves have strong designability. For example, the selection of components and the control of layer thickness can give full play to the regulation of performance by the interface. In addition, nano-layered materials whose components are mostly immiscible can form a clear heterogeneous interface at the atomic scale, which is conducive to the study of interface effects. In addition, a large number of studies have shown that high-entropy alloy films / coatings in BCC structures exhibit excellent antioxidant properties, corrosion resistance and radiation resistance similar to alloys under irradiation conditions, which is one of the effective ways to prepare protective films / coatings for cladding materials.

[0004] In summary, for nano-layered materials, the interface structure is one of the important factors that determine their performance. It is of great research significance to regulate their comprehensive performance, including mechanics, radiation damage resistance, and thermal stability, by designing the interface structure. However, the current methods for preparing nano-layered materials with various interface structures are very limited and the comprehensive performance of the prepared materials is poor. Therefore, it is necessary to study a method for preparing nano-layered materials with different interface structures to improve the comprehensive performance of nano-layered materials. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a MoNbZr / Zr nano-layered material and a preparation method thereof. The nano-layered material prepared by the interface regulation process has high purity, the deposited nano-layered material is uniform and dense, and the interface bonding force is strong, thereby improving the comprehensive performance of the nano-layered material.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0008] Step 1, removing impurities and oxide film on the surface of the silicon substrate;

[0009] Step 2: In a high vacuum environment, the etched silicon substrate is sputtered alternately using a MoNbZr target and a Zr target, and after sputtering and deposition to a preset thickness, the sputtering is cooled to room temperature in the furnace to obtain a MoNbZr / Zr nano-layered material;

[0010] In each modulation cycle, the formed MoNbZr component layer and Zr layer have the same thickness, which is 5nm-75nm, and the thickness of the MoNbZr / Zr nano-layered material is less than 1.4um-1.6um.

[0011] Preferably, in step 1, the polished silicon substrate is ultrasonically cleaned in acetone and anhydrous ethanol in sequence and then dried to remove impurities on the surface of the silicon substrate;

[0012] Then, the dried silicon substrate is etched with a hydrofluoric acid aqueous solution to remove the oxide film on the surface.

[0013] Preferably, the vacuum degree of the high vacuum environment in step 2 is less than 4.0×10 -4 Pa.

[0014] Preferably, in step 2, the power of the MoNbZr target and the Zr target is 200 W, the argon gas flow rate during the deposition process is 60 sccm, and the gas pressure is 1.0 Pa.

[0015] Preferably, in step 2, the sputtering time of the MoNbZr target and the Zr target in each modulation cycle are 40 to 580 seconds and 30 to 400 seconds respectively.

[0016] Preferably, in step 2, under vacuum conditions, the substrate surface is first etched using Ar+ ions, and then pre-sputtering is performed, the argon gas is introduced for at least 30 seconds before pre-sputtering, and the pre-sputtering time is at least 10 seconds.

[0017] Preferably, in step 2, the rotation speed of the silicon substrate during the magnetron sputtering deposition process is 15 r / min.

[0018] A MoNbZr / Zr nano-layered material comprises alternately stacked MoNbZr component layers and Zr layers, wherein the thickness of the MoNbZr component layers and the Zr layers in each modulation period are the same, the thickness of the MoNbZr / Zr nano-layered material is about 1.5 μm, and the hardness of the MoNbZr / Zr nano-layered material is 5.25 GPa to 6.95 GPa.

[0019] Preferably, when the thickness of the MoNbZr layer and the pure Zr layer in one modulation period are 5 nm respectively, the interlayer interface type formed by sputtering is a crystal / crystal incoherent type; the internal structure of the MoNbZr layer is a two-phase structure of alternating crystals and amorphous phases;

[0020] When the thickness of the MoNbZr layer and the pure Zr layer in a modulation period are 10 to 75 nm respectively, the interlayer interface type formed by sputtering is a crystal / crystal incoherent type, and the MoNbZr layer is a dual-phase structure in which the crystal is "embedded" in the amorphous.

[0021] Preferably, the element ratio in the MoNbZr alloy component layer is Mo:Nb:Zr=1:1:1.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects:

[0023] The present invention is a preparation method of a MoNbZr / Zr nano-layered material. First, impurities and oxide films on the surface of a silicon substrate are removed by ultrasonic cleaning and etching, so that metal atoms and silicon atoms are directly combined, which is conducive to the oriented epitaxial growth of a composite material. Then, under the action of positive and negative electrode voltages, Ar gas between the electrodes is ionized in large quantities, so that Ar atoms are ionized into Ar+ and electrons. The electrons are accelerated to fly to the substrate of the anode, and the positively charged Ar+ flies quickly to the target material of the cathode under the action of the electric field and the magnetic field, bombarding the target material and causing elastic collision with sample (MoNbZr / Zr) atoms, transferring part of the kinetic energy, thereby exciting and generating dislocated atoms. The dislocated atoms further collide with the surrounding sample atoms repeatedly in sequence to generate a collision cascade. When the collision cascade reaches the sample surface, the kinetic energy of the atoms far exceeds their surface binding energy, so that they escape into the vacuum to form steam. The sample atoms move in reverse to the substrate (anode) for deposition, and the high-density plasma such as secondary electrons with lower energy generated by the collision circulates in the form of a cycloid under the combined action of mutually perpendicular electromagnetic fields, without contacting the substrate. The present invention adopts magnetron sputtering for sequential deposition, which improves the ionization rate and the deposition rate. The scattering effect of the working gas on the sputtered atoms is weak, and the deposition efficiency and the layer interface bonding force are further improved. Therefore, the deposition rate is fast, the ionization efficiency is high, the prepared nano-layered material has high purity, and the deposited nano-layered material is uniform and dense, has few defects, high purity and strong interface bonding force.

[0024] This method uses alloying strategies to increase the compositional complexity of BCC structural alloys, especially multi-principal medium (high) entropy alloys, which have been proven to effectively suppress radiation-induced defects. This phenomenon is attributed to the compositional complexity and lattice distortion effect of medium (high) entropy alloys, which can effectively change the migration behavior of defects, thereby improving their radiation resistance. In addition, the nano-layered materials prepared by magnetron sputtering can control the layer thickness and increase the interface by changing the sputtering time. The interface is an effective trap for absorbing dislocations and capturing defects generated during the irradiation process. The presence of grain boundaries / interfaces reduces the mean free path of defect migration and reduces the density of free migration defects. Therefore, nano-layered materials with high-density interfaces help improve radiation resistance.

[0025] Furthermore, the interface structure of the MoNbZr / Zr nano-layered material is adjusted by controlling the deposition time. During the deposition process, the collision probability between the sputtered Mo atoms, Nb atoms, and Zr atoms in the MoNbZr alloy target is high, and the energy when deposited on the substrate is large, so a partially metastable amorphous structure will be formed, but the overall structure is still crystalline. The sputtered Zr atoms in the Zr target are deposited to form a crystal layer, and the interface structure is a crystal / crystal type. With the change of deposition time, the single layer thickness of the nano-layered material MoNbZr / Zr changes, but it is worth noting that the interlayer interface still maintains a crystal / crystal incoherent interface, indicating that its interface structure is very stable. In addition, the MoNbZr layer still maintains a crystal / amorphous dual-phase structure. The difference is that when the deposition time is short, the layer interface has a restraining effect on the growth of the grains, and the grain size is small. When the deposition time is long, the grain size increases, and the alternating dual-phase structure of crystal / amorphous in the MoNbZr layer changes to a dual-phase structure in which the crystal is "embedded" in the amorphous. Layer thickness and interface are important factors affecting the performance and deformation mechanism of nano-layered materials. The critical shear stress required for dislocation transmission in the crystal / amorphous portion will affect the hardness of the sample. When the layer thickness is small, in the crystal / amorphous alternating phase, the amorphous layer is approximately "transparent" to the dislocation movement. Therefore, the layered material of the crystal / amorphous alternating phase has low hardness and good plasticity. However, the layered material in which the crystal is "embedded" in the amorphous structure has high hardness and poor plasticity. At the same time, the interface is an effective defect absorption trap that can absorb defects caused by helium ions and the like. Therefore, the MoNbZr / Zr nano-layered material with a multi-interface structure is of great guiding significance for the development of corrosion-resistant materials and radiation-resistant materials, and for exploring the movement laws of dislocations at different interface structures.

[0026] Furthermore, after the deposition is completed, the film is naturally cooled in a high vacuum coating chamber to stabilize the layer interface structure and avoid the shedding of the nano-layered material due to the difference in the thermal expansion coefficient of the material and possible oxidation under high temperature conditions.

[0027] A MoNbZr / Zr nano-layered material, which has a columnar crystal morphology and a stable size within the nano-crystal range; the interface structure and mechanical properties change with the thickness of the layer: when the layer thickness is small, the MoNbZr layer is a crystal / amorphous alternating structure with low hardness; when the layer thickness is large, the MoNbZr layer is a crystal "embedded" in an amorphous structure with high hardness. The layer is uniform and dense, and the comprehensive performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD spectrum of the MoNbZr / Zr nano-layered material prepared by magnetron sputtering in the present invention.

[0029] Figure 2 This is a TEM cross-sectional view of the MoNbZr / Zr nanolayered material prepared by magnetron sputtering in the present invention.

[0030] Figure 3 This is a graph showing the nanoindentation hardness results of the MoNbZr / Zr nanolayered material with different modulation periods of the present invention. DETAILED DESCRIPTION

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings, which are intended to explain the present invention rather than to limit it.

[0032] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0033] Step 1, removing impurities and oxide film on the surface of the silicon substrate;

[0034] Specifically, the silicon substrate is first polished, and then the polished silicon substrate is ultrasonically cleaned in acetone and anhydrous ethanol in turn and then dried to remove impurities on the surface of the silicon substrate; then, the dried silicon substrate is corroded by a hydrofluoric acid aqueous solution for 60 seconds to remove the oxide film on its surface.

[0035] Step 2: In a high vacuum environment, first use Ar+ ion etching to further remove impurities on the substrate surface; then turn on the MoNbZr target and Zr target DC power supplies in turn for pre-sputtering and formal sputtering. Only one target power supply is turned on in each modulation cycle. After the two components are alternately deposited to a preset thickness, a nano-layered material composed of MoNbZr and Zr alternating is obtained during furnace cooling.

[0036] Specifically, the power of Ar+ ion etching is 200 W, and the etching time is at least 5 minutes; the argon gas is introduced for at least 30 seconds before pre-sputtering; and the pre-sputtering time is at least 10 seconds.

[0037] The MoNbZr target power is set to 200W, and the purity is not less than 99.9wt.%; the Zr target power is set to 200W, and the purity is not less than 99.9wt.%. During the deposition process, the argon gas flow rate is set to 60sccm, and the gas pressure is set to 1.0Pa; during the deposition process, the silicon substrate rotation speed is 15r / min; the sputtering time is 40±5s and 30±5s, 80±5s and 50±5s, 190±5s and 130±5s, or 390s-270s and 580s-400s. The element ratio in the MoNbZr alloy component layer is Mo:Nb:Zr≈1:1:1.

[0038] like Figure 1-Figure 3 As shown in the figure, the prepared MoNbZr / Zr nano-layered material has a columnar grain morphology and a stable size within the nano-crystalline range; the interface structure and mechanical properties change with the thickness of the layer: when the layer thickness is small, the MoNbZr layer is a crystal / amorphous alternating structure with low hardness; when the layer thickness is large, the MoNbZr layer is a crystal "embedded" in an amorphous structure with high hardness. The layer is uniform and dense, with excellent comprehensive performance. The thickness of the nano-layered material is about 1.5μm, uniform and dense, with excellent comprehensive performance.

[0039] The preparation method of the MoNbZr / Zr nano-layered material comprises the following steps: firstly, the Si-(111) substrate after single-side polishing is immersed in acetone and anhydrous ethanol solution for ultrasonic cleaning for at least 15 minutes to remove organic stains and dust on the surface, thereby improving the interface bonding force. Then, the treated substrate is immersed in a hydrofluoric acid aqueous solution for etching for about 60 seconds to remove oxides on the substrate surface, thereby facilitating the oriented epitaxial growth of the nano-layered material. The MoNbZr / Zr nano-layered material is deposited on the clean substrate surface by magnetron sputtering technology, and the principle is that Ar+ ions bombard the target material (cathode) and elastically collide with the sample (MoNbZr / Zr) atoms, transferring part of the kinetic energy, thereby exciting the generation of dislocated atoms. The dislocated atoms further collide with the surrounding sample atoms repeatedly in sequence to generate a collision cascade. When the collision cascade reaches the sample surface, the kinetic energy of the atoms far exceeds their surface binding energy, thereby escaping into the vacuum to form steam. The sample atoms move in the opposite direction to the substrate (anode) for deposition, while the high-density plasma such as secondary electrons with lower energy generated by the collision moves in a cycloidal manner under the combined action of mutually perpendicular electromagnetic fields without contacting the substrate. The magnetron sputtering deposition technology is adopted, and both the MoNbZr target and the Zr target use a DC power supply with a power of 200W. The grain size of the MoNbZr / Zr nano-layered material is adjusted by controlling the deposition time, thereby changing the distribution of the crystal / amorphous phases in the MoNbZr layer. When the deposition time is short, the MoNbZr layer is a crystal / amorphous alternating structure. When the deposition time is long, the grain size in the MoNbZr layer increases, and the crystal is "embedded" in the amorphous structure. Finally, it is naturally cooled in a high vacuum coating chamber to avoid the shedding of the nano-layered material due to the different thermal expansion coefficients of the materials. The nano-layered material is prevented from being oxidized when in contact with air under high temperature, and finally a MoNbZr / Zr nano-layered material with different modulation periods and different structures is formed.

[0040] Example 1

[0041] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0042] S1, using acetone and anhydrous ethanol to remove impurities on the surface of the target material and the substrate in turn, and then using a hydrofluoric acid aqueous solution to remove impurities and oxides on the surface of the target material and the substrate.

[0043] S2, use conductive glue to fix the substrate on the base plate, and mechanically and automatically escort it into the magnetron sputtering vacuum coating chamber, pump it to the back vacuum degree of 3.6×10-4Pa and start etching. The etching power is 200W and the time is 5min.

[0044] S3, after the etching is completed, formal sputtering begins: first, argon gas is introduced for 30 seconds, pre-sputtering is performed for 10 seconds, and then MoNbZr / Zr nano-layered materials are sequentially sputtered on the clean silicon substrate using a dual DC power supply;

[0045] The power of the MoNbZr target (purity 99.95wt.%) and the Zr target (purity 99.99wt.%) were both 200W, the argon gas flow rate was 60sccm, the deposition pressure was set to 1.0Pa, the deposition temperature was room temperature, the substrate speed was 15r / min, the MoNbZr target power supply and the Zr target power supply were turned on in sequence for deposition, the deposition time of the MoNbZr target in one modulation cycle was 40s, the deposition time of the Zr target was 30s, the deposition was cyclically deposited 150 times, and the total deposition time was 14400s;

[0046] S4, wait for the sample to cool naturally in the high vacuum coating chamber for 2-3 hours to room temperature, and then exit to obtain a nanocrystalline MoNbZr / Zr nanolayered material with a modulation period thickness of λ=10nm, a MoNbZr layer thickness of hA=5nm (A-MoNbZr), and a Zr layer thickness of hB=5nm (B-Zr). The thickness of the nanolayered material is about 1.5μm.

[0047] The microstructure characterization and mechanical properties testing of the prepared MoNbZr / Zr nanolayered material showed that the grains were columnar, the interlayer interface type was crystal / crystal incoherent, the MoNbZr layer was a crystal / amorphous alternating structure, and its hardness was measured to be 5.25±0.04GPa by nanoindentation under a load of 6000μN.

[0048] Example 2

[0049] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0050] S1, using acetone and anhydrous ethanol to remove impurities on the surface of the target material and the substrate in turn, and then using a hydrofluoric acid aqueous solution to remove impurities and oxides on the surface of the target material and the substrate.

[0051] S2, use conductive glue to fix the substrate on the base plate, and mechanically and automatically escort it into the magnetron sputtering vacuum coating chamber, pump it to the back vacuum degree of 2.4×10-4Pa and start etching. The etching power is 200W and the time is 5min.

[0052] S3, after the etching is completed, formal sputtering begins: first, argon gas is introduced for 30 seconds, pre-sputtering is performed for 10 seconds, and then MoNbZr / Zr nano-layered materials are deposited on the clean silicon substrate by sputtering in sequence using dual DC power supplies, wherein the power of the MoNbZr target (purity 99.95wt.%) and the Zr target (purity 99.99wt.%) are both 200W, the argon gas flow rate is 60sccm, the deposition pressure is set to 1.0Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, and the MoNbZr target power supply and the Zr target power supply are turned on in sequence for deposition. In one modulation cycle, the deposition time of the MoNbZr target is 80s, and the deposition time of the Zr target is 50s. The deposition is repeated 75 times, and the total deposition time is 11700s.

[0053] S4, after the sample is naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature, a nanocrystalline MoNbZr / Zr nanolayered material with a modulation period thickness of λ=20nm, a MoNbZr layer thickness of hA=10nm, and a Zr layer thickness of hB=10nm is obtained. The thickness of the nanolayered material is about 1.5μm.

[0054] The microstructure characterization and mechanical property testing of the prepared MoNbZr / Zr nano-layered material showed that the grains were columnar, the interlayer interface type was crystal / crystal incoherent, the MoNbZr layer was a crystal "embedded" in an amorphous structure, and its hardness was measured to be 5.51±0.06GPa by nanoindentation under a load of 6000μN.

[0055] Example 3

[0056] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0057] S1, using acetone and anhydrous ethanol to remove impurities on the surface of the target material and the substrate in turn, and then using a hydrofluoric acid aqueous solution to remove impurities and oxides on the surface of the target material and the substrate.

[0058] S2, use conductive glue to fix the substrate on the base plate, and mechanically and automatically escort it into the magnetron sputtering vacuum coating chamber, pump it to the back vacuum degree of 3.2×10-4Pa and start etching. The etching power is 200W and the time is 5min.

[0059] S3, after the etching is completed, formal sputtering begins: first, argon gas is introduced for 30 seconds, pre-sputtering is performed for 10 seconds, and then MoNbZr / Zr nano-layered materials are deposited on the clean silicon substrate by sputtering in sequence using dual DC power supplies, wherein the power of the MoNbZr target (purity 99.95wt.%) and the Zr target (purity 99.99wt.%) are both 200W, the argon gas flow rate is 60sccm, the deposition pressure is set to 1.0Pa, the deposition temperature is room temperature, the substrate speed is 15r / min, and the MoNbZr target DC power supply and the Zr target DC power supply are turned on in sequence for deposition. In one modulation cycle, the deposition time of the MoNbZr target is 190s, and the deposition time of the Zr target is 130s. The deposition is repeated 30 times, and the total deposition time is 10380s.

[0060] S4, after the sample is naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature, a nanocrystalline MoNbZr / Zr nanolayered material with a modulation period thickness of λ=50nm, a MoNbZr layer thickness of hA=25nm, and a Zr layer thickness of hB=25nm is obtained. The thickness of the nanolayered material is about 1.5μm.

[0061] The microstructure characterization and mechanical property testing of the prepared MoNbZr / Zr nano-layered material showed that the grains were columnar, the interlayer interface type was crystal / crystal incoherent, the MoNbZr layer was a crystal "embedded" in an amorphous structure, and its hardness was measured to be 6.95±0.07 GPa by nanoindentation under a load of 6000μN.

[0062] Example 4

[0063] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0064] S1, using acetone and anhydrous ethanol to remove impurities on the surface of the target material and the substrate in turn, and then using a hydrofluoric acid aqueous solution to remove impurities and oxides on the surface of the target material and the substrate.

[0065] S2, use conductive glue to fix the substrate on the base plate, and mechanically and automatically escort it into the magnetron sputtering vacuum coating chamber, pump it to the back vacuum degree of 2.7×10-4Pa and start etching. The etching power is 200W and the time is 5min.

[0066] S3, after the etching is completed, formal sputtering begins: first, argon gas is introduced for 30 seconds, pre-sputtering is performed for 10 seconds, and then MoNbZr / Zr nano-layered materials are deposited on the clean silicon substrate by sputtering in sequence using dual DC power supplies, wherein the power of the MoNbZr target (purity 99.95wt.%) and the Zr target (purity 99.99wt.%) are both 200W, the argon gas flow rate is 60sccm, the deposition pressure is set to 1.0Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, and the MoNbZr target DC power supply and the Zr target DC power supply are turned on in sequence for deposition. The deposition time of the MoNbZr target in one modulation cycle is 390s, and the deposition time of the Zr target is 270s. The deposition is repeated 15 times, and the total deposition time is 10290s.

[0067] S4, after the sample is naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature, a nanocrystalline MoNbZr / Zr nanolayered material with a modulation period thickness of λ=100nm, a MoNbZr layer thickness of hA=50nm, and a Zr layer thickness of hB=50nm is obtained. The thickness of the nanolayered material is about 1.5μm.

[0068] The microstructure characterization and mechanical property testing of the prepared MoNbZr / Zr nano-layered material showed that the grains were columnar, the interlayer interface type was crystal / crystal incoherent, the MoNbZr layer was a crystal "embedded" in an amorphous structure, and its hardness was measured to be 6.55±0.06GPa by nanoindentation under a load of 6000μN.

[0069] Example 5

[0070] A method for preparing a MoNbZr / Zr nano-layered material comprises the following steps:

[0071] S1, using acetone and anhydrous ethanol to remove impurities on the surface of the target material and the substrate in turn, and then using a hydrofluoric acid aqueous solution to remove impurities and oxides on the surface of the target material and the substrate.

[0072] S2, use conductive glue to fix the substrate on the base plate, and mechanically and automatically escort it into the magnetron sputtering vacuum coating chamber, pump it to the back vacuum degree of 1.0×10-4Pa and start etching. The etching power is 200W and the time is 5min.

[0073] S3, after the etching is completed, formal sputtering begins: first, argon gas is introduced for 30 seconds, pre-sputtering is performed for 10 seconds, and then MoNbZr / Zr nano-layered materials are deposited on the clean silicon substrate by sputtering in sequence using dual DC power supplies, wherein the power of the MoNbZr target (purity 99.95wt.%) and the Zr target (purity 99.99wt.%) are both 200W, the argon gas flow rate is 60sccm, the deposition pressure is set to 1.0Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, and the MoNbZr target power supply and the Zr target power supply are turned on in sequence for deposition. The deposition time of the MoNbZr target in one modulation cycle is 580s, and the deposition time of the Zr target is 400s. The deposition is repeated 10 times, and the total deposition time is 10060s.

[0074] S4, after the sample is naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature, a nanocrystalline MoNbZr / Zr nanolayered material with a modulation period thickness of λ=150nm, a MoNbZr layer thickness of hA=75nm, and a Zr layer thickness of hB=75nm is obtained. The thickness of the nanolayered material is about 1.5μm.

[0075] The microstructure characterization and mechanical properties testing of the prepared MoNbZr / Zr nano-layered material showed that the grains were columnar, the interlayer interface type was crystal / crystal incoherent, the MoNbZr layer was a crystal "embedded" in an amorphous structure, and its hardness was measured to be 6.38±0.14 GPa by nanoindentation under a load of 6000μN.

[0076] The invention discloses a MoNbZr / Zr nano-layered material and a preparation method thereof. The MoNbZr / Zr nano-layered material is prepared by depositing on a clean silicon substrate by a magnetron sputtering deposition method. Ar+ ions bombard a target material (cathode) to cause elastic collisions with sample (MoNbZr / Zr) atoms, further generating collision cascades, whereby the sample atoms are excited and reversely deposited on the substrate. MoNbZr atoms and Zr atoms are deposited in sequence to alternately form multilayer nano-layered materials with different modulation periods, different interface structures and different phase compositions, and high-density plasma such as secondary electrons generated by sputtering circulates in the form of cycloids under the combined action of mutually perpendicular electromagnetic fields without contacting the substrate. Therefore, the ionization efficiency is high and the deposition rate is fast. The invention not only successfully prepares nano-layered materials with different interface structures, but also the obtained nano-layered materials are uniform and dense, with clear interface structures and excellent comprehensive performance.

[0077] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a MoNbZr / Zr nano-layered material, characterized in that: The following steps are involved: Step 1, removing impurities and oxide film on the surface of the silicon substrate; Step 2: In a high vacuum environment, the etched silicon substrate is sputtered alternately using a MoNbZr target and a Zr target, and after sputtering and deposition to a preset thickness, the sputtering is cooled to room temperature in the furnace to obtain a MoNbZr / Zr nano-layered material; In each modulation cycle, the MoNbZr component layer and the Zr layer formed have the same thickness, which is 5 nm -75 nm, and the thickness of the MoNbZr / Zr nanolayered material is 1.4 μm -1.6 μm; The element ratio in the MoNbZr component layer is Mo:Nb:Zr=1:1:1; The power of the MoNbZr target and the Zr target is 200 W, the argon gas flow rate is 60 sccm, and the gas pressure is 1.0 Pa during the deposition process; the sputtering time of the MoNbZr target and the Zr target in each modulation cycle is 40-580 s and 30-400 s, respectively.

2. The method for preparing a MoNbZr / Zr nano-layered material according to claim 1, characterized in that: In step 1, the polished silicon substrate is ultrasonically cleaned in acetone and anhydrous ethanol in sequence and then dried to remove impurities on the surface of the silicon substrate; Then, the dried silicon substrate is etched with a hydrofluoric acid aqueous solution to remove the oxide film on the surface.

3. The method for preparing a MoNbZr / Zr nano-layered material according to claim 1, characterized in that: The vacuum degree of the high vacuum environment in step 2 is less than 4.0×10 -4 Pa.

4. The method for preparing a MoNbZr / Zr nano-layered material according to claim 1, characterized in that: In step 2, under vacuum conditions, the substrate surface is first etched using Ar+ ions, and then pre-sputtering is performed. The argon gas is introduced for at least 30 s before pre-sputtering, and the pre-sputtering time is at least 10 s.

5. The method for preparing a MoNbZr / Zr nano-layered material according to claim 1, characterized in that: In step 2, the rotation speed of the silicon substrate during the magnetron sputtering deposition process is 15 r / min.

6. A MoNbZr / Zr nano-layered material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It comprises alternately stacked MoNbZr component layers and Zr layers, the thickness of the MoNbZr component layers and the Zr layers in each modulation period are the same, the thickness of the MoNbZr / Zr nano-layered material is 1.5 μm, and the hardness of the MoNbZr / Zr nano-layered material is 5.25 GPa to 6.95 GPa.

7. A MoNbZr / Zr nano-layered material according to claim 6, characterized in that: When the thickness of the MoNbZr component layer and the pure Zr layer in one modulation cycle are 5 nm respectively, the interlayer interface type formed by sputtering is a crystal / crystal incoherent type; the internal structure of the MoNbZr component layer is a two-phase structure of alternating crystals and amorphous phases; When the thickness of the MoNbZr component layer and the pure Zr layer in a modulation period are 10~75 nm respectively, the interlayer interface type formed by sputtering is crystal / crystal incoherent type, and the MoNbZr component layer is a dual-phase structure in which the crystal is "embedded" in the amorphous.

Citation Information

Patent Citations

  • Coated cutting tool

    CN101164772A

  • Coating of light-water reactor

    CN109913823A